Sequence stratigraphic framework of K-field in part of Western Niger delta, Nigeria (2011)
"A sequence stratigraphic approach was applied to K-Field, within the western Niger Delta by integrating wireline logs of four wells; 001,003, 004 and 005; and high resolution biostratigraphic data of wells 001, 004 and well 005. The study is aimed at deducing key bounding surfaces, depositional sequences and their corresponding systems tracts as well as the palaeodepositional environment of the hydrocarbon bearing Agbada Formation in the study area. Two sequence boundaries at 8900 ft (2697 m) and 9050 ft (2742 m), and one maximum flooding surface at a depth of 7650 ft (2318 m) were recognized in well 5 and used to subdivide the stratigraphic succession into depositional sequences and their corresponding systems tracts. Highstand and Transgressive systems tracts were recognized in each of the three depositional sequences. Marker shale, characterized by Chloguebelina 3 (16.0 Ma) was used to date the key bounding surfaces with the aid of the Niger Delta chronostratigraphic chart as Early to Late Miocene. The Highstand systems tracts are characterized by shale-rich upward coarsening sands, having poor reservoir quality while the lowstand systems tracts are characterized by thick sandstone units, indicating good quality seals to reservoirs. From the SP logs motifs, the depositional environments inferred include tidal channel, shoreface and shelf environments which typify a marine depositional setting. "